Efecto de la inclusión parcial de harina de cáscara de maní en el comportamiento productivo de cerdos en preceba - Renteria Capa, Dayanna Abigail (2023)
This study focuses on the evaluation of peanut shell meal as an alternative feed source for pigs, with the goal of improving profitability for medium and large pig producers. The main objective of this research was to determine the effects of the inclusion of peanut shell meal in the diet of pigs on feed intake, weight gain, and feed conversion, as well as to analyze its economic impact. The methodological approach adopted was quantitative and experimental, involving three treatments with different levels of peanut shell meal inclusion in the pig diet. The results obtained indicate that the treatment with 3% peanut shell meal achieved higher feed intake, weight gain, and feed conversion efficiency compared to the other treatments. In economic terms, the treatment with the highest inclusion of peanut shell meal proved to be the most profitable, followed by the treatment with 1.5% inclusion. On the other hand, the treatment without peanut shell meal inclusion was less cost-effective. In conclusion, this study has shown that the inclusion of peanut shell meal in pig feed can improve production performance and profitability for medium and large pig farmers. The results obtained can serve as a basis for the implementation of more efficient and sustainable feeding strategies in the swine industry.